THE PHYSIOTHERAPIST WILL BE REPLACED BY ROBOT? - Bogdan-Alexandru Hagiu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The paper reviews the types of medical robots used in recovery and their advantages and limitations. The aim is to estimate the prospects of medical robotics in physiotherapy. From the results of research conducted on groups of patients who received conventional therapy and robotic medical therapy, it appears that the best results are obtained by combining them. However, comparisons depend on the conditions and types of tests used. For example, in arm hemiparesis after stroke the recovery with robots is without additional benefits from a functional perspective. Moreover, the robot can not interact effectively with the patient and the adjust of operating parameters must be permanent. The conclusion is that in the recovery of skeletal and muscle damage the human factor is indispensable.